Efficacy of a two bag acetylcysteine regimen to treat paracetamol overdose (2NAC study). (March 2020) - Wong, Anselm; Isbister, Geoff; McNulty, Richard; Isoardi, Katherine; Harris, Keith; Chiew, Angela; Greene, Shaun; Gunja, Naren; Buckley, Nicholas; Page, Colin; Graudins, Andis
Abstract: Background: Previous studies of paracetamol overdose treatment show that a 2-bag, 20-h intravenous (IV) acetylcysteine regimen decreased the incidence of non-allergic anaphylactic reactions compared to the 3-bag, 21 h IV regimen, but have not examined efficacy of the 20-h 2 bag regimen. Methods: This was a multi-centre observational study of paracetamol overdose presentations treated with a 2-bag IV acetylcysteine regimen (200 mg/kg over 4 h, 100 mg/kg over 16 h) compared to a 3-bag regimen, performed from 2009 to 2019. Patients were referred from the emergency department to the inpatient toxicology units for continued management. For the primary non-inferiority analysis: subjects had single, acute ingestions, a serum paracetamol-concentration performed 4 to 8-h post-ingestion. The primary outcome was development of acute liver injury (ALI), defined as peak ALT>150 U/L; and > double admission baseline ALT (for presentations within 24 h post-overdose). Secondary outcomes included adverse reactions to acetylcysteine (cutaneous and systemic). Finding: Out of 6419 paracetamol overdoses, 2763 received acetylcysteine. For the primary analysis, 1003 received the 2-bag and 783 the 3-bag acetylcysteine regimen. When presentation bloods were performed 4 to 8-h post-overdose, 21 (3.1%) developed ALI with the 2-bag regimen vs 16 (2.9%) with the 3-bag regimen (Difference: 0.2%, 95%CI:-1.6 to 2.2). The incidence of hepatotoxicity was: 1.2% ( n  = 8) with the two-bag regimen and 1.6% ( n  = 9) with the three-bag regimen (Difference -0.4%, 95%CI -1.75, 0.91). When presentation bloods were performed 8 to 24-h post-overdose, 70 (21%) developed ALI with the 2-bag regimen vs 46 (23%) with the 3-bag regimen (Difference: -2%, 95%CI -9.12 to 5.36). There were significantly less cutaneous and systemic non-allergic anaphylactic reactions recorded after treatment with the two-bag than the three-bag regimen (1.3% [ n  = 17] and 7.1% [ n  = 65], Difference: -5.8%, 95%CI -7.6 to -4.0, p  < 0.0001), respectively. Interpretation: A two-bag intravenous acetylcysteine regimen was found to be non-inferior to the three-bag regimen with regards to efficacy in preventing acute liver injury for early presentations of paracetamol overdose. No important differences were seen for any other presentations. The two-bag regimen also decreased the incidence of both non-allergic anaphylactic reactions and gastrointestinal adverse events from acetylcysteine treatment. Funding: AW is funded by a National Health and Medical Research Council (NHMRC) Early Career Fellowship ID 1159907. GI is funded by a NHMRC Senior Research Fellowship ID 1061041. The NHMRC had no role in the design, writing of this manuscript. The corresponding author (AW) had full access to all the data in the study and final responsibility for the decision to submit the manuscript for publication.